Dissolution and a “Universe of Solutions”: Deliberate Disruptions, Ever-Changing Repetition, and Vocal Prosody in Björk’s Vulnicura - Malawey, Victoria (Circuit)

(untitled) (Circuit, musiques contemporaines, 2021)
Björk’s Vulnicura (2015) engages the theme of the dissolution of a long-term relationship. As with much of Björk’s music, most listeners are drawn to her voice and the interplay between lyrics and vocal delivery. This article explores vocal prosody, conceived as the pacing and flow of delivery, in three tracks—“Lionsong,” “Black Lake,” and “Family”—through aspects of discontinuous phrasing, varied metric placement, melismatic embellishment, consonantal articulation, and vocal layering. Thinking about the sonic materiality of the voice broadly—and more specifically, understanding the prosodic aspects of Björk’s delivery on Vulnicura—help us probe the album’s expressivity and grasp the specific material elements that facilitate its emotional content. Though most prosodic elements on this album reflect Björk’s singing style more broadly, some—such as discontinuous phrasing—are intensified to specifically serve this album’s emotive aims.